(untitled) (Mongolian Journal of Agricultural Sciences, 2018)
Aim of this survey was to reveal the feasibility to develop the Community (Village level) based breeding program in Khovd province. Erdeneburen sum was selected due to the most affected area with the degradation of pasture in this province (Report of Green Gold Project, 2015), where 34 goat herders were interviewed from 4 bags. According to the educational level of herders, the larger proportion of the respondents had lower secondary (56%) and higher level. The remaining 11.7% of them were finished the primary school. This result revealed that the herders were very knowledgeable, so that potential opportunity seen for the recording of goats by them. Total of 150; 50 bucks, 3 castrated males and 97 female goats were used for the baseline survey of quantitative and qualitative traits. In the studied flocks, the large proportions of goats were red (59%) and black (67%) , but white , grey and combination with other colours were few or 4, 4.7, 7.3% respectively, all observed goats had short coarse hairs and with short spiry horns. Sex and age strongly influenced (P<0.001) body weight, other linear body measurements and cashmere fineness. Chest girth has high correlation to cashmere yield and cashmere fineness. There was a strict seasonal mating with control and avoidance of inbreeding by keeping bucks in the same flock for 2 years and practiced the buying bucks from east and north regions. Therefore, the genetic structure of goats should be clarified at first, then appropriate breeding program need to be designed in this sum.